1970
DOI: 10.1029/ja075i022p04266
|View full text |Cite
|
Sign up to set email alerts
|

Energy spectra of precipitating electrons from observations of optical aurora, Bremsstrahlung X rays, and auroral absorption

Abstract: Simultaneous balloon observations of auroral N2+ (λ3914) emission and bremsstrahlung X rays produced by the precipitation of energetic electrons in the auroral zone suggest that two distinct groups of electrons are responsible for the observed effects. One group is responsible for the major portion of the total precipitated energy during visible aurora, and at times this group not only provides the dominant flux of X rays below about 40 kev but also accounts for most of the cosmic noise absorption. A remarkabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1971
1971
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…et at., 1975] and spectra With two exponential components, hard and soft, have also been observed[Christensen and Karas, 1970]. Even• i is the only event where the onset'is observed, that is, in adjacent 15-rain spectra the X-ray spectra went from background to a detectable predpitation flux.…”
mentioning
confidence: 89%
“…et at., 1975] and spectra With two exponential components, hard and soft, have also been observed[Christensen and Karas, 1970]. Even• i is the only event where the onset'is observed, that is, in adjacent 15-rain spectra the X-ray spectra went from background to a detectable predpitation flux.…”
mentioning
confidence: 89%
“…Figure 6 shows plots of the integral electron fluxes measured at Vela and at ATS 1 and calculated from the X-ray flux at the balloon for three times, 0930, 0933, and 0935 UT, just before and during the 'spike.' (An incident electron spectrum was derived from the measured X-ray spectrum using the method of Christensen and Karas [1970]). The calculated electron fluxes above the balloon at 0933 and 0935 are indicated by two straight-line segments because the X-ray data suggested that the incident electron flux at those times could best be represented as a superposition of two exponential spectra.…”
Section: Because Of the General Similarity Of Development Of The Subsmentioning
confidence: 99%